H-doped PbTiO3: Structure and electronic properties - Stashans, A. (2006)
The geometry and electronic properties of the interstitial H atom in the tetragonal PbTiO3 crystal have been studied using an advanced quantum chemical computer code developed for the modeling of crystals. The inserted H atom was found to bind to one of the O atoms and to form the hydroxyl, O - H group, with the inter-atomic distance equal to 0.93 and 1.00 for the hydroxyls containing O atom in the dimerized and nondimerized Ti - O - Ti chains, respectively. Atomic displacements in the vicinity of O - H complex are calculated and analyzed in relation to the H-produced changes upon the atomic charges in defective region. The role of H impurity on the ferroelectric polarization in the tetragonal PbTiO3 is discussed in terms of the results obtained in our research and those presented in the other studies on this subject. © 2006 Wiley Periodicals, Inc.